COMPARATIVE STUDY BETWEEN ULTRASOUND-GUIDED TRANSVERSE ABDOMINIS PLANE VERSUS POSTERIOR RECTUS SHEATH BLOCK FOR POSTOPERATIVE ANALGESIA IN MIDLINE LAPAROTOMIES (The Research of Medical Science Review, 2025)
Background: Experiencing pain is very common after laparotomy in the midline. TAP and PRS blocks, performed while using ultrasound guidance, are used for regional anesthesia to lessen opioid use and help patients recover more quickly. Objective: To find out whether the mean postoperative NRS score is lower after ultrasound-guided TAP than after PRS blocks in patients who have had laparotomy through the midline. Study Design: A Randomized Controlled Trial Place and Duration of study. Department of Anesthesia Rahman Medical Institute Peshawar from For six months from December 2020 through May 2021 Methods: This study conducted at the Department of Anesthesia Rahman Medical Institute Peshawar from For six months from December 2020 through May 2021.out of 138 patients, all within 18 to 50 years, having a midline laparotomy. Participants were randomly assigned to receive TAP or PRS block while guided by ultrasound. Pain after the operation was measured using a NRS questionnaire at several times, with the primary outcome checked at 12 hours. Results: The mean age of patients in the group was 39.4 years, with a ±8.2 year standard deviation. By 12 hours, PRS block group patients reported lower NRS scores on average compared to the TAP block group patients (p < 0.05). There were no serious adverse incidents during this operation. The outcomes did not change significantly with changes in gender or length of procedure. Conclusion: For patients undergoing midline laparotomy, ultrasound-guided posterior rectus sheath block gives more effective postoperative pain control than TAP block and should therefore be part of every enhanced recovery program.